Algorithmic Art: Shuffling Space and Time: Art-Science Dialogues and a Techno-Saga. Issue 2 (1st June 2019) - Lai, Linda Chiu-han
Abstract : Why are art-science dialogues important, and how should they take place? How do our everyday culture and institutional constructs define and delimit such possibilities? Why do contemporary art lovers still presume they are immune to and from scientific knowledge? How should a visitor of a media art event make sense of the machine work? Algorithmic Art: Shuffling Space & Time (AA) directed these questions to technical experts, artists, art lovers, and the public through a series of themed discussions and a six-hundred-square-meter indoor playground of machines and computational installations. AA also sought to key in on the question of survival. What mark has the struggling existence of the twenty-year-old School of Creative Media at the City University of Hong Kong left to Hong Kong's (media) art history? The school remains the only pedagogic research center in Hong Kong where conceptual issues of new media art creation and how to "live" in an age of big data are interrogated through scholarship and practice.